2021
DOI: 10.1097/md.0000000000024951
|View full text |Cite
|
Sign up to set email alerts
|

Systemic inflammatory response to non-surgical treatment in hypertensive patients with periodontal infection

Abstract: Hypertension is associated with chronic inflammation in the tissues and organs that are involved in the regulation of arterial pressure, such as kidneys and blood vessels. Periodontal disease affects systemic inflammatory markers, leading to endothelial dysfunction, atherosclerotic plaque instability, dyslipidaemia, and insulin resistance. These conditions can also cause an increase in the blood pressure. Nonsurgical periodontal therapies, such as scaling and root planning, can affect systemic markers of infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 23 publications
3
6
1
Order By: Relevance
“…Studies that evaluated the effect of NSPT on systemic BP are controversial [22, 25-28, 48, 49, 56]. Some studies have demonstrated a BP improvement after NSPT [25][26][27], whereas other studies did not show such improvements [28,48,49,56]. In the present study, in the analysis of systemic BP variables, no significant reductions were observed after NSPT at 90 and 180 days compared to baseline.…”
Section: Discussioncontrasting
confidence: 61%
See 3 more Smart Citations
“…Studies that evaluated the effect of NSPT on systemic BP are controversial [22, 25-28, 48, 49, 56]. Some studies have demonstrated a BP improvement after NSPT [25][26][27], whereas other studies did not show such improvements [28,48,49,56]. In the present study, in the analysis of systemic BP variables, no significant reductions were observed after NSPT at 90 and 180 days compared to baseline.…”
Section: Discussioncontrasting
confidence: 61%
“…Of importance, 5 out 12 interventional studies confirmed a reduction in blood pressure levels following periodontal therapy, ranging from 3 to 12.5 mmHg of SBP and from 0 to 10 mmHg of DBP [24]. These findings parallel observation made by previous studies showing that patients subjected to non-surgical periodontal treatment (NSPT) showed improved periodontal clinical parameters and reduced plasma levels of inflammatory markers [25][26][27][28]. Vidal et al (2011) found that periodontitis is a risk indicator for hypertensive patients, and there are indications that systemic inflammation is associated with both conditions [29].…”
Section: Of 13supporting
confidence: 70%
See 2 more Smart Citations
“…In a study by Konopka, Pietrzak and Brzezińska-Błaszczyk, (32), the levels of GCF IL-8 in patients with periodontal inflammatory diseases, reduced from the range of 7.4 to 96.1pg/ml to 2.7 ± 20.3 pg/ml at 4 weeks of intervention and was significantly lower than at baseline (p-value <0.001). Escobar Arregocés et al, (33) evaluated the systemic pro-inflammatory markers levels in hypertensive patients with periodontal conditions. Although the result of their study shows reduced levels of IL-6 (from 0.31 ± 0.18pm/ml to 0.24 ± 0.13pg/ml) and IL-8 (from 9.17 ± 1.05pg/ml to 7.79 ± 0.62pg/ml) but not statistically significant.…”
Section: Discussionmentioning
confidence: 99%